The implications of educational games on the development of children's intellectual abilities - Izat, Meruyert; Kyyakbayeva, Ulbossyn; Nurgaliyeva, Saniya; Urinova, Feruzakhon; Khallokova, Maksudakhon (International Journal of Innovative Research and Scientific Studies, 2025)
Educational games have emerged as powerful tools in contemporary pedagogy, leveraging interactive and engaging platforms to enhance children's intellectual abilities. This research explores the multifaceted implications of educational games on cognitive development focusing on critical thinking, problem-solving skills and knowledge retention among children. This study used a mixed-data collection strategy. The goal of this research was to determine the impact of developed educational game technology on improving children's intellectual abilities. The study included 43 participants. According to the study, children have an average level of intellectual development. In this regard, training preschool-aged children required modifications to the content, procedural and personal aspects of learning for children using educational game technology. The study's findings revealed that incorporating educational game technological advances into the process of training children improved their cognitive abilities. Teachers can improve their teaching strategies using the useful tools and materials provided by the study's findings on the usage of educational games to support children' intellectual development. This research underscores the importance of integrating educational games into curricula to maximize their intellectual benefits and prepare children for future academic and life challenges.